Thymic Hypertrophy and Sudden Unexpected Death In Adults –A Retrospective Study Of 56 Autopsy Cases - Zou, Liping; Zhang, Ye; Zhu, Rong (International Journal of Human Anatomy, 2017)
Status thymico-lymphaticus had ever been explained as a cause of sudden death usually in children, but few cases were reported in adults. We sought to determine the relationship between thymic hypertrophy and sudden unexpected death in adult (SUDA), and associated macroscopic and microscopic findings. Adult post mortems from 1984 to 2014 were reviewed and 23 thymic hypertrophy patients without SUDA, 33 thymic hypertrophy patients with SUDA and 172 SUDAs without thymic hypertrophy entered. The data of thymus, lymph nodes, spleen, heart, aorta, and adrenal glands were collected for macroscopic and histological analysis. Ten antibodies were used and applied to 3 children and 46 adult thymus specimens. We found, as an independent factor, thymic hypertrophy increased significantly the risk of SUDA (6.9 folds) in both male and female. What’s more, SUDAs associated with thymic hypertrophy were quite younger (22.5 years) than those without it. A majority of patients with hypertrophic thymus had a variable number of accompanied anomalies described as the typical characteristics of status thymico-lymphaticus, but no macroscopic and microscopic findings related to SUDA in patients with thymic hypertrophy. Cytokeratins (CKs) showed distinctly different immunohistochemical expression patterns in individuals who had different death causes and disease background. Instead of a disease entity “status thymico-lymphaticus” is a systematic abnormality with thymic hypertrophy as a feature involving mainly immune and/or cardiovascular system, probably caused by gene mutations.
Keywords: Thymic hypertrophy; Sudden unexpected death; Status thymico-lymphaticus